«МЕДВЕЖИЙ ПРАЗДНИК» У НИВХОВ ПО АРХИВНЫМ МАТЕРИАЛАМ КОЛЛЕКЦИИ Ч.М. ТАКСАМИ В НАЦИОНАЛЬНОЙ БИБЛИОТЕКЕ РЕСПУБЛИКИ САХА (ЯКУТИЯ) : THE NIVKHS TRADITIONAL «BEAR HOLIDAY» - ARCHIVE MATERIALS FROM THE COLLECTION OF C. M. TAKSAMI OF THE NATIONAL LIBRARY OF THE SAKHA REPUBLIC (YAKUTIA) AS A CASE-STUDY - Ханды-Стручкова Л В, (ECHO OF THE ARCTIC ODYSSEY: THE FATES OF ETHNIC CULTURES IN THE STUDIES OF NORTHERN SCIENTISTS. Сборник материалов Всероссийской научно-практической конференции с международным участием, 2019)
В статье рассказывается об архивных материалах коллекции Таксами Ч.М. ученого-сибиреведа, действительного члена Российской Академии естественных наук, заслуженного деятеля науки Республики Саха (Якутия). Уникальная коллекция Таксами содержит 2467 документов, она формировалась трудами ученого на протяжении многих десятилетий во время многочисленных экспедиций к коренным народам Якутии, Хабаровского и Красноярского краев, Мурманской и Амурской областей, Сахалина, Камчатки, Чукотки, Ямала, Обского Севера. В статье дается подробная биографическая справка владельца коллекции, также аудиовизуальных и рукописных документах нивхского народа. В статье подробно описываются материалы из архива Таксами Ч. М. по медвежьему празднику нивхов. : The article describes the scientific collection of books and archive documents of C.M. Taksami, a scholar, who specialized in Siberian research, and was a full member of the Russian Academy of Natural Sciences, an Honored Scholar of the Sakha Republic (Yakutia). Taksamis unique collection contains 2467 documents. It was formed from a collection of his works which he had written over many decades during numerous expeditions to the indigenous peoples of Yakutia, the Khabarovsk and Krasnoyarsk territories, the Murmansk and Amur regions, Sakhalin, Kamchatka, Chukotka, Yamal, the Ob North. The collection reflects stages of the scholars life and his world view. The article provides detailed biographical information about the scholar. These are the types of publications presented in the collection and examples of documents. The content of the collection documents is analyzed in this article. The article describes in detail the materials from the archive of C.M. Taksami devoted to the Nivkhs Bear Festival.